The importance of preventive training actions for the reduction of workplace accidents within the Spanish construction sector - Romero Barriuso, Alvaro; Villena Escribano, Blasa María; Rodríguez Saíz, A. (Safety Science, 2021)
The degree of compliance with occupational risk-prevention legislation among Construction Sector firms within Spain, most of which are micro-SMEs and SMEs, is studied in this research. Likewise, a meticulous analysis is completed of all aspects that are related with the training of workers within the Construction Sector. Information is collected through a survey administered to an accumulated sample of 250 workers, referring to the indicators that are directly related to the principal causes of accident rates in construction. Numerous firms participated in this study, led by High-level Risk-Prevention Technicians. The results highlighted the serious shortcomings existing within the field of preventive actions and worker training, motivated in large part by the severe crisis of the Construction Sector in Spain that began in 2008, some important consequences of which live on, reflecting high occupational accident rates. The investigation concludes with proposals to overcome these contingencies, referring especially to the need to strengthen professionalization within the Construction Sector, to improve training actions in prevention matters, and to encourage firms to work towards efficient compliance with the safety regulations.
Keywords: safety training; construction sector; occupational risk-prevention; preventive culture; reduction of occupational accident rates; JCR; Scopus